Giant-Cell Tumor of the Distal Ulna Treated by Wide Resection and Ulnar Support Reconstruction: A Case Report. (7th June 2010) - Minami, Akio; Iwasaki, Norimasa; Nishida, Kinya; Motomiya, Makoto; Yamada, Katsuhisa; Momma, Daisuke
Abstract : Giant-cell tumor of bone occurred in the distal end of the ulna is extremely uncommon. A 23-year-old male had a giant-cell tumor occurred in the distal end of the ulna. After wide resection of the distal segment of the ulna including giant-cell tumor, ulnar components of the wrist joint were reconstructed with modified Sauvé-Kapandji procedure using the iliac bone graft, preserving the triangular fibrocartilage complex and ulnar collateral ligament in order to maintain ulnar support of the wrist, and the proximal stump of the resected ulna was stabilized by tenodesis using the extensor carpi ulnaris tendon. One year after operation, the patient's wrist was pain-free and had a full range of motion. Postoperative X-rays showed no abnormal findings including recurrence of the giant-cell tumor and ulnar translation of the entire carpus. The stability of the proximal stump of the distal ulna was also maintained.